Between Pain and Math : How Expectations Shape Cognitive Processes from Neural Activity to Behaviour. - Schwarz, Katharina (Logos Verlag Berlin, 2015)
Long description: Expectancy effects are a wide-spread phenomenon, influencing cognitive operations from basic stimulus processing to higher cognitive functions. Their influence often goes unnoticed, even though it leaves a lasting fingerprint on perception and behaviour. The present work aims at providing an improved framework for understanding the impact of expectations by fusing two major fields of research on this question: the study of traditional placebo effects in clinical settings and of social expectancies such as stereotype-related beliefs. Behavioural patterns and physiological mechanisms underlying the phenomena are identified and compared to current models of stereotype and placebo effects. The presented findings give new insights on the effects of expectations on cognition, and represent a first step to identify basic global mechanisms underlying different forms of the phenomena.